2023
DOI: 10.55489/njcm.140120232528
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Of Depression And Associated Factors Among Elderly Population In A Rural Area Of Kozhikode District, North Kerala.

Abstract: Background: Old age is often accompanied by frailty and diseases including neuropsychiatric disorders. Demen-tia and depression are the most common neuropsychiatric disorders among the elderly. Kerala has the maximum proportion of elderly in its population and successful identification of the elderly at risk is important for early in-tervention. The purpose of the study is to estimate the prevalence of depression and associated factors among the elderly population. Methods: A cross-sectional study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Various studies have shown the prevalence of spiritual involvement as 76.4-94.7% (4)(5)(6). Many studies in developed countries have observed an association between spiritual practices and health especially among the elderly population (7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown the prevalence of spiritual involvement as 76.4-94.7% (4)(5)(6). Many studies in developed countries have observed an association between spiritual practices and health especially among the elderly population (7)(8).…”
Section: Introductionmentioning
confidence: 99%